Implementation of LQR and LQT to Improve Energy Efficiency and Performance of DC Motor Control Systems in Support of Community Empowerment Programs - Naufal Hariz (Politeknik Perkapalan Negeri Surabaya, 2023)
The implementation of Linear-Quadratic Regulator (LQR) and Linear-Quadratic Tracker (LQT) is an effective method for optimizing the performance of DC motor control systems. This study aims to evaluate the performance of LQR and LQT in controlling the speed of DC motors using microcontrollers. The control system comprises a speed sensor, a microcontroller, and a DC motor, integrated to ensure efficient and reliable operation. The results indicate that the implementation of LQR and LQT significantly enhances the stability of DC motor control systems by reducing overshoot and achieving faster settling times compared to the PID control method. Additionally, LQT demonstrates superior speed tracking accuracy over LQR, as evidenced by a lower mean squared error. These findings are particularly relevant for community empowerment programs where energy-efficient and cost-effective technologies are crucial. For example, implementing LQT-controlled DC motors can optimize energy usage in agricultural tools, creative industries, and education-focused initiatives in underserved communities. By bridging advanced control technology and practical applications, this research contributes to the development of sustainable, energy-efficient solutions that support community development programs. These results serve as a reference for further applications of LQR and LQT in other DC motor control systems within community service projects.